2021
DOI: 10.1145/3460287
|View full text |Cite
|
Sign up to set email alerts
|

Towards Interconnected Blockchains

Abstract: Unprecedented attention towards blockchain technology is serving as a game-changer in fostering the development of blockchain-enabled distinctive frameworks. However, fragmentation unleashed by its underlying concepts hinders different stakeholders from effectively utilizing blockchain-supported services, resulting in the obstruction of its wide-scale adoption. To explore synergies among the isolated frameworks requires comprehensively studying inter-blockchain communication approaches. These approaches broadl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 44 publications
0
18
0
1
Order By: Relevance
“…Later on, Belchior et al [11] stated that although some critical requirements on blockchain interoperability were fulfilled primary on public blockchain solutions, private and private-topublic interoperability is still a challenge that needs further work. A more recent paper by Lohachab et al [12] states that there is a need to develop new interoperability solutions that include private and consortium blockchain networks.…”
Section: Blockchain Interoperability Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Later on, Belchior et al [11] stated that although some critical requirements on blockchain interoperability were fulfilled primary on public blockchain solutions, private and private-topublic interoperability is still a challenge that needs further work. A more recent paper by Lohachab et al [12] states that there is a need to develop new interoperability solutions that include private and consortium blockchain networks.…”
Section: Blockchain Interoperability Analysismentioning
confidence: 99%
“…In order to start developing interoperability solutions, we first needed to understand the existing ones, their definitions and features. Some interoperability frameworks and classifications exist and have classified them with quite success [9,11,12]. Unfortunately, interoperability solutions evolve very fast and classifications become quickly outdated.…”
Section: Blockchain Interoperability Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, there are two studies that survey BC interoperability found in [61] focusing on IoT and [80] for general BC interoperability. Compared to the former, we differentiate our survey introducing broader coverage than IoT.…”
Section: Bc Interoperability In Bpsmentioning
confidence: 99%